Is The Ramayana a Work of World Literature? The History, Translation, Anthologization, Circulation, Distribution, and Production of The Ramayana - Scolastika Wedhowerti (Journal of Language and Literature, 2014)
The notion of world literature (Weltliteratur) was first introduced by Johann Wolfgang von Goethe in 1827. It is a concept which peoples of different nations read each others works either in their original language or translation. The Ramayana, a great Indian epic, has existed for more than two millennia. It has been a subject of discussion of whether it is a work of world literature or not. There are factors contributing to the concept of world literature, namely anthologization, history, translation, circulation, distribution, and production. This paper aims at answering the question of whether the Ramayana is a work of world literature or not.Keywords: anthologization, translation, production, world literature